Kajian Filsafat Hukum Mengenai Pembatasan Waktu Kuasa Jual Tanpa Dasar Hukum Formal - Darbe Tyas Waskitha; Selamat Widodo; Endang Eko Wati (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The power of attorney to sell in civil law is rooted in the principle of freedom of contract as stipulated in Article 1338 of the Indonesian Civil Code. However, inpractice, powers of attorney to sell are often made absolute, irrevocable, and without a time limit, and are even attached to loan agreements as security for debt repayment. Such practices give rise to juridical and philosophical issues because they shift the essence of a power of attorney from representation into a disguised transfer of rights, and potentially cause injustice to the grantor of the power. The Supreme Court of the Republic of Indonesia, through various decisions, has consistently rejected the validity of absolute powers of attorney, particularly those used as debt security, and has affirmed that a power of attorney to sell cannot serve as a basis for the transfer of land rights. This research employs a normative legal research method with philosophical, conceptual, and statutory approaches. The study focuses on the philosophical legitimacy of imposing a time limitation on powers of attorney to sell in notarial practice and land administration, despite the absence of explicit regulation in the Civil Code or land law regulations. The findings show that limiting the duration of a power of attorney to sell has strong philosophical legitimacy based on the theories of legal certainty, justice, and utility as articulated by Hans Kelsen, Gustav Radbruch, Aristotle, John Rawls, Jeremy Bentham, and John Stuart Mill. The decisions of the Supreme Court are consistent with these legal philosophical values, as they function as corrective instruments to prevent circumvention of the law and to protect weaker parties. Therefore, the imposition of a time limitation on a power of attorney to sell can be philosophically and juridically justified as an effort to maintain a balance of rights and obligations between the parties, even though it lacks an explicit written normative basis.